THE EFFECT OF CHEWING GUM ON FEELING HUNGRY IN HEMODIALISA PATIENTS AT Dr. M. YUNUS HOSPITAL BENGKULU IN 2023 - Mardiani Mardiani; Vira Dwi Rizky; Dahrizal; Husni; Erni Buston; Widia Lestari (Poltekkes Kemenkes Bengkulu, 2023)
Chronic renal failure is the deterioration of kidney function, which, over time, will be increasingly damaged and cannot be repaired so that the body fails to maintain metabolic, fluid, and electrolyte balance. Thirst is one of the problems often encountered in patients undergoing hemodialysis with fluid restriction. Thirst is typically responded to by drinking, but patients with renal failure are not allowed to respond the usual way to the thirst experienced. Therefore, thirst management is essential. One thirst management that can be applied to respond to thirst is chewing gum to reduce thirst in chronic renal failure patients undergoing hemodialysis. Hemodialysis patients experience thirst, which causes discomfort and affects quality of life; chewing gum (peppermint) is an intervention that can be used to reduce thirst. This study aimed to determine the effect of chewing gum on thirst in hemodialysis patients. The research design used is a quasi-experiment with a one-group pre-test design. The sampling technique was purposive sampling with a total sample of 35 respondents. The intervention group was given chewing gum. The thirst assessment instrument uses the Thirst Distress Scale (TDS) assessment instrument. Research results: The average thirst before chewing gum (22.34) is severe. After being given the intervention for three days, the patient's thirst decreased to (12.91) mild thirst. Analysis using the Wilcoxon test with a p-value of 0.000 ? < 0.05, where there is a significant effect of chewing gum on thirst in hemodialysis patients at Dr. M Yunus Bengkulu Hospital.